Friendly visiting and partial enquiry (proof copy)
1902-02 1902 1900s 15 pages 13 Judged able to pay a specialist Sent away 3 Discharged themselves 12 — 15 Total 158 Cases referred to C.O.S. Assisted 60 Not assisted 24 Withdrawn 15 Still pending decision 3 — 102 Various kinds of assistance given by C.O.S. Convalescent treatment 29 Open-air treatment 7 Help in the home 9 Letter for Brompton 1 False teeth 6 Surgical boots 5 Other instruments 3 — 60 Assisted by various agencies and individuals. By clergy 15 By district workers 6 By individual workers 7 By West London Mission 2 By House of Charity 2 By relations 1 — 33 Referred to M.A.B.Y.S. 6 C.E.T.S. 7 Church Army 1 S.P.C.C. 1 — 15 Loans advanced for instruments. Repaid 10 Repaying 4 Loans advanced for convalescent treatment. Repaid 3 (No bad debts.) — 17 PARTIAL INQUIRIES MADE BY C.O.S. 19 Statement at hospital true. Eligible for treatment and continued to attend 7 No further action taken, as patient did not return 5 — 12 Statement at hospital false. Returned and sent away 1 No further action taken, as patient did not return 6 — 7 Result not yet known 1 20 378/IMSW/A/1/1/9